Untethered kirigami soft robots with programmable locomotion - Wang, Jinqiang (2024)
Kirigami can induce shape transformations in planar and nonplanar geometry by rational cut design, significantly increasing the kinematics degree of freedom. Here, we exploit kirigami metamaterials and hard-magnetic actuation to design untethered soft robots. The kirigami soft robot, consisting of slit perforated kirigami patterns with embedded hard-magnetic disks in each facet, exhibits modularity, scalability, and programmable locomotion. By varying the magnetization arrays, the kirigami soft robots show diverse static and dynamic behaviors, which are systematically studied by experiments and FEM. We demonstrate multi-module soft robots with programmable locomotion, where directional locomotion is generated by a synergistic effect and circular motion is realized by the asymmetric pattern. Active and passive environmental adaptabilities and multifunctionalities are shown, including passing over gaps, active obstacle avoidance, moving over various substrates, carrying loads, remote circuit switches, and amphibious motions by bistability. This work paves the way to design untethered soft robots with programmable motions and multifunctionalities.